Comparative Study of Treatment of Adhesive Capsulitis of Shoulder: Corticosteroid Versus Corticosteroid with Hydro Distension (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To compare the effectiveness of Intra-articular corticosteroid versus intra-articular corticosteroid with hydro-distension.Methods: This randomized control trial study was conducted January 2014 to December 2016. The primary outcome was percentage reduction in the Shoulder pain and disability index (SPADI).Total one thousand patients diagnosed clinically were divided into two groups A and B. Group A received 40mg Triamcinolone injection, 4ml of contrast medium (ultravist), 3ml 2% Lidocaine and distension was done with 10 to 20ml of 0.9% normal saline. Group B was treated with intra articular 40mg Triamcinolone injection, 4ml of contrast medium (ultravist), 3ml 2% Lidocaine. SPADI was measured before and after giving of injections. Patients were followed up for three months and SPADI was measured at third week and sixth week.Results: The Pretreatment mean SPADI score of Group A patients was noted as 79.99±3.54 whereas the mean SPADI score of Group B patients was 81.50±3.01. The mean SPADI score of patients at 6th week post treatment of Group A noted as 26.83±2.62 and mean SPADI score of Group B was 34.32±1.67. Statistically all follow up treatments are highly significant according to the study groups i.e. p-value=0.000*.Conclusion: We concluded that as far as percentage reduction in SPADI is concerned a little difference between hydro-distension and intra-articular corticosteroid injection alone, which help to reduce the pain and disability in frozen shoulder. But Hydro-distention is slightly superior in reducing Pain and Disability.